MIXED-MODE FRACTURE PERFORMANCE OF FIBER-REINFORCED CONCRETE UNDER IMPACT LOADING - ARSLAN, A (E & Fn Spon, 1995)
A test procedure developed to determine the mixed-mode impact resistance of fibre reinforced concrete materials is described. Results are presented from a series of experiments using a repeated drop-weight impact apparatus for the impact resistance of both polypropylene and steel fibre reinforced concrete. The behaviour of the mixed-mode specimen geometry was investigated under impact loading condition. The effect of the fibre types and contents on the impact fracture energy of the specimens was investigated. A close investigation was made of the positions and formations of the crack patterns. The fracture performance of the plain and fibre reinforced concrete was investigated with the proposed geometry using 1.0, 2.0 and 3.0%, by weight in the case of steel fibre, and 0.1, 0.2 and 0.3% by weight in the case of polypropylene fibre.